Into the unknown : how great explorers found their way by land, sea, and air - Ross, Stewart; Biesty, Stephen (Somerville, Mass. : Candlewick Press, 2011)
From Pytheas the Greek, who sailed to the Artic Circle without a compass, to Neil Armstrong landing on the moon--here are fourteen extraordinary journeys by land, sea, and air. Each one is remarkable for the way it was made, for the technology behind it, and for the inspiration it gave to future generations. Through grippling storytelling, fantastic fold-out cross sections, detailed maps, and remarkable technical drawings--join the world's bravest explorers on some of the greatest journeys ever made!
Keywords: Explorers -- Juvenile literature; Discoveries in geography -- Juvenile literature